2009
DOI: 10.1007/s11249-009-9498-3
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Tribomaterial During Sliding: A Brief Introduction

Abstract: This brief introductory article summarizes key findings from experiments and from computer simulations concerning the dramatic changes that commonly occur adjacent to sliding interfaces. We conclude that a wide range of observed features depends on a few basic processes (plastic deformation, interactions with the environment (including the counterface) and mechanical mixing) and that sliding leads to flow patterns similar to those expected in fluid flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(93 citation statements)
references
References 20 publications
5
88
0
Order By: Relevance
“…We cannot answer these complex questions based on our experimental results; nevertheless, we can present a hypothesis based on a relatively simple model developed by Rigney et al [37]. They used molecular dynamics to simulate the sliding between two amorphous surfaces with different hardness and elastic moduli.…”
Section: Discussionmentioning
confidence: 95%
“…We cannot answer these complex questions based on our experimental results; nevertheless, we can present a hypothesis based on a relatively simple model developed by Rigney et al [37]. They used molecular dynamics to simulate the sliding between two amorphous surfaces with different hardness and elastic moduli.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, a recent review indicated that deviations from Archard's law may take place owing to the large plane strains at the contact points and the adhesive transfer and mechanical mixing [7]. Several reports on the tribological behavior of copper [8][9][10] demonstrate the complex nature of wear; specifically, the wear rate may be a function of numerous parameters. Moreover, it was demonstrated very recently that significant grain refinement, and consequently, strengthening, may not lead to improved wear properties in commercial pure copper but rather to an increase in the steady-state wear rate with a consequent decrease in the electroconductivity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the materials response during running-in, Rigney et al investigated the involved mechanisms leading to changes in near-surface structure and to the introduction of foreign elements as result of intermixing processes [3,[5][6][7]. The third body is the prerequisite for ultra-low wear rates and small coefficients of friction.…”
Section: Introductionmentioning
confidence: 99%